Engravings and rock coatings at Pudjinuk Rockshelter No. 2, South Australia. (April 2018) - Roberts, Amy; Burke, Heather; Pring, Allan; Zhao, Jing; Gibson, Christopher T.; Popelka-Filcoff, Rachel S.; Thredgold, Joanne; Bland, Catherine; ,
Abstract: This paper presents the results of analyses of rock coatings from Pudjinuk Rockshelter No. 2 in South Australia (SA) using the following methods: 1) Raman microscopy; 2) X-ray powder diffraction; and 3) Scanning electron microscopy coupled with integrated energy dispersive X-ray spectroscopy. The deposits analysed contained a mixture of thenardite, glauberite, halite, sylvinite, gypsum, probable palygorskite and amorphous carbon. The engravings previously extant at the rockshelter are also described and contextualised. This article provides the first record of thenardite in any context in SA. It is argued that the accumulation of the salt crystals, likely caused or exacerbated by run-off from irrigation, led to significant haloclasty (salt weathering) that caused or contributed to the destruction of the pre-contact petroglyphs in the rockshelter. The presence of amorphous carbon is interpreted as possibly deriving from firewood sources. The effects of salt weathering on petroglyphs in the Murray River Gorge, as demonstrated in this paper, reveals the urgent need for a systematic program of rock art recording in the region. Highlights: Analyses of rock coatings from Pudjinuk Rockshelter No. 2 in South Australia Methods employed: 1) Raman microscopy; 2) XRD; and 3) SEM EDS Damage to rock engravings by haloclasty